Computational framework for the selection of energy solutions in indigenous communities in Colombia: Kanalitojo case study. Issue 1 (1st January 2021) - Colmenares-Quintero, Ramón Fernando; Latorre-Noguera, Luis Fernando; Rojas, Natalia; Kolmsee, Karl; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos
Abstract: This study seeks to analyze different energy solutions for the Kanalitojo Indigenous Community that is located 25 kilometers from the municipal seat of the municipality of Puerto Carreño, in the State of Vichada, eastern Colombia. For the development of this study, a technical performance analysis has been applied to each proposed solution considering the amount of electricity generation and demand. The first solution refers to a hydrokinetic turbine connected to a distribution network. The second solution combines the use of solar panels, hydrokinetic turbine, and portable batteries with which it is possible to transport the generated energy to the places where the community needs it. The third proposed energy solution refers to the use of micro-cogeneration units and portable batteries. With the use of the capabilities of the TRNSYS v17 energy simulation software, the comparative technical analysis between each solution for the same load demand is carried out. This analysis has shown a great advantage in the use of solar panels, hydrokinetic turbine, and portable batteries with an electricity surplus of 103.8%. However, technically the first solution based on a hydrokinetic turbine is more suitable for the community challenges due to it meets the electricity demand of the community by an excess of 12.4% and the capital and operating expenditure are less.